Income Distribution and the Allocation of Public Agricultural Investment in Developing Countries - Karp, Larry (Washington, DC: World Bank, 2012)
Public investment in infrastructure or education can increase agricultural productivity, leading to higher rural wages and higher returns to farmers. These investments also induce the reallocation of factors of production. This paper, which studies both the traditional and modern agricultural sector, finds that investment increases productivity in the sector where it is made, and it can also affect the other sector via adjustments of factors of production.